1995
DOI: 10.1111/j.1471-6402.1995.tb00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Women's Studies Courses on Gender-Related Attitudes of Women and Men

Abstract: Attitudes about feminism, gender equality, and gender differences were assessed for male and female students enrolled in three women's studies courses and four control courses at the beginning and end of an academic semester. Compared to control students, women's studies students agreed more with feminist and equality items, and disagreed more with gender difference items, at the beginning of the term. Nonetheless, belief in gender differences decreased among men, but not women, enrolled in women's studies cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 7 publications
3
30
1
Order By: Relevance
“…Our findings also partially support those of Thomsen et al (1995), Bargad and Hyde (1991), and Henderson-King and Stewart (1999) that female college students' enrollment in a women's studies course increased self-identification as feminist. Twenty of the 30 participants in our study had taken a college course that deals with issues of gender.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings also partially support those of Thomsen et al (1995), Bargad and Hyde (1991), and Henderson-King and Stewart (1999) that female college students' enrollment in a women's studies course increased self-identification as feminist. Twenty of the 30 participants in our study had taken a college course that deals with issues of gender.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, in a study of female students in a women's studies course, Henderson-King and Stewart (1999) found that women's levels of feminist self-identification increased over the course of the semester; similar increases were not found in a comparison group of students who were not enrolled in women's studies. Whereas the feminist attitudes of the male college students decreased, the feminist attitudes of the female students increased in Thomsen, Basu, and Reinitz's (1995) study of students enrolled in a women's studies course.…”
mentioning
confidence: 92%
“…The few empirical studies which measure the effectiveness of feminist pedagogy show that non-traditional learning does create long-term change among students Feminist pedagogy and student resistance 43 (Vedovato & Vaughter, 1980;Bargad & Hyde, 1991;Stake & Rose, 1994;Thomsen et al, 1995). These studies generally find that after participation in a class organized around feminist pedagogy, students (especially female students- Thomsen et al, 1995) are likely to self-identify as feminists and become more active in issues related to women.…”
Section: What Does Feminist Pedagogy Bring To the Issue Of Moral Dichmentioning
confidence: 93%
“…These studies generally find that after participation in a class organized around feminist pedagogy, students (especially female students- Thomsen et al, 1995) are likely to self-identify as feminists and become more active in issues related to women. These findings hold true when students from women's studies classes are interviewed one year after completion of the course (Stake & Rose, 1994), and when women's studies classes are compared to other classes without a feminist pedagogy yet with discussions about gender (Bargad & Hyde, 1991).…”
Section: What Does Feminist Pedagogy Bring To the Issue Of Moral Dichmentioning
confidence: 98%
“…Notes 1 Similar results were not discernible among male students who were enrolled in the same courses (Thomasen et al, 1995). 2 When making this statement we are referring to background of students attending institutions of higher education, not to the population at large.…”
Section: Resultsmentioning
confidence: 92%